Encyclopedia Brown and the case of the jumping frogs - Sobol, Donald J., 1924- (New York : Yearling/Random House, 2003)
Encyclopedia Brown, boy detective extraordinaire, solves ten new cases, including "The Case of the Miracle Pill," "The Case of Nemo's Tuba," "The Case of the Lawn Mower Races," and "The Case of the Air Guitar." Solutions provided at the end of each chapter.
600
Keywords: Mystery and detective stories